Pemberdayaan Masyarakat Membuat Bakso Bandeng di Kelurahan Unyur, Serang, Banten - Dabella Yunia; Chandra Prasadhita; Dien Muhammad Salam (Universitas Serang Raya, 2020)
This society aims to increase community creativity which provides economic added value for milkfish. This activity is carried out by inviting the community to be given an entrepreneurial presentation, then providing training to make milkfish milkfish. Milkfish meatballs are added value with contemporary packaging, namely in cup packaging. This is a strategic business and at the same time raised local resources.